2021
DOI: 10.3390/jdb9030034
|View full text |Cite
|
Sign up to set email alerts
|

The Role of RNA-Binding Proteins in Vertebrate Neural Crest and Craniofacial Development

Abstract: Cranial neural crest (NC) cells delaminate from the neural folds in the forebrain to the hindbrain during mammalian embryogenesis and migrate into the frontonasal prominence and pharyngeal arches. These cells generate the bone and cartilage of the frontonasal skeleton, among other diverse derivatives. RNA-binding proteins (RBPs) have emerged as critical regulators of NC and craniofacial development in mammals. Conventional RBPs bind to specific sequence and/or structural motifs in a target RNA via one or more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 97 publications
(146 reference statements)
0
12
0
Order By: Relevance
“…The RNA-binding protein Elavl1 is expressed in cranial neural crest Cranial neural crest cells are indispensable for proper craniofacial development (van Limborgh et al, 1983;Vega-Lopez et al, 2018). Whereas transcription factors have been well established critical regulators of neural crest development and craniofacial morphogenesis [reviewed in (Gou et al, 2015)], growing evidence indicates an essential role for post-transcriptional regulation in these processes (Cibi et al, 2019;Copeland and Simoes-Costa, 2020;Dennison et al, 2021;Forman et al, 2021). To identify RNA-binding proteins with potential roles in cranial neural crest specification, we analyzed single cell RNA-sequencing (scRNA-seq) data for cranial neural crest isolated from avian embryos at the 5-6 somite stage (Williams et al, 2019); we identified three distinct clusters (neural, premigratory (pNC), and delaminating/migratory (mNC)) among which genes associated with the gene ontology (GO) term "binds to 3' UTR" were differentially expressed (Figure 1A-E).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The RNA-binding protein Elavl1 is expressed in cranial neural crest Cranial neural crest cells are indispensable for proper craniofacial development (van Limborgh et al, 1983;Vega-Lopez et al, 2018). Whereas transcription factors have been well established critical regulators of neural crest development and craniofacial morphogenesis [reviewed in (Gou et al, 2015)], growing evidence indicates an essential role for post-transcriptional regulation in these processes (Cibi et al, 2019;Copeland and Simoes-Costa, 2020;Dennison et al, 2021;Forman et al, 2021). To identify RNA-binding proteins with potential roles in cranial neural crest specification, we analyzed single cell RNA-sequencing (scRNA-seq) data for cranial neural crest isolated from avian embryos at the 5-6 somite stage (Williams et al, 2019); we identified three distinct clusters (neural, premigratory (pNC), and delaminating/migratory (mNC)) among which genes associated with the gene ontology (GO) term "binds to 3' UTR" were differentially expressed (Figure 1A-E).…”
Section: Resultsmentioning
confidence: 99%
“…The transcriptional control of these events has been dissected and mapped into modules of a feed-forward gene regulatory network (GRN), which helps explain the detailed sequence of events involved in neural crest development ( Martik and Bronner, 2017 ; Simões-Costa and Bronner, 2015a ; Williams et al, 2019 ). Recently, in addition to transcriptional events, there has been growing appreciation for the role that post-transcriptional regulation plays in the establishment, maintenance, and regulation of neural crest formation ( Bhattacharya et al, 2018 ; Cibi et al, 2019 ; Copeland and Simoes-Costa, 2020 ; Forman et al, 2021 ; Sánchez-Vásquez et al, 2019 ; Ward et al, 2018 ; Weiner, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Many RBPs are known to be ubiquitously expressed and we show that they have generally low Gini scores in our multi-tissue analysis (Figure S7D). It is therefore likely that their function is not directly regulated by transcription, but instead may be important for post-transcriptional processing of genes that are either specifically expressed or expressed in cell types like migrating neural crest that are particularly sensitive to perturbation (Forman et al, 2021).…”
Section: Differential Expression During Craniofacial Development Iden...mentioning
confidence: 99%
“…15 RBM10 is one of the RNA-binding proteins that participates in neural crest and craniofacial development. 16 Specifically, RBM10 is highly expressed in the first bronchial arch which gives rise to the mandible. 17 This mimics the high expression of SOX9 and collagen II in the developing mandible.…”
Section: E Tarp Syndrome (Omim 311900)mentioning
confidence: 99%